2016
DOI: 10.3390/ijerph13050481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meteorological Parameters and PM10 on the Incidence of Hand, Foot, and Mouth Disease in Children in China

Abstract: Hand, foot, and mouth disease (HFMD) is a globally-prevalent infectious disease. However, few data are available on prevention measures for HFMD. The purpose of this investigation was to evaluate the impacts of temperature, humidity, and air pollution, particularly levels of particulate matter with an aerodynamic diameter 10 micrometers (PM10), on the incidence of HFMD in a city in Eastern China. Daily morbidity, meteorological, and air pollution data for Ningbo City were collected for the period from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
3
41
3
Order By: Relevance
“…The coefficient between PM 2.5 and HFMD is -0.37 while PM10 is -0.33. Our study is not consistent with the conclusion in the previous study (10), which showed no significant relationship between PM10 and HFMD (10).…”
Section: Discussioncontrasting
confidence: 99%
“…The coefficient between PM 2.5 and HFMD is -0.37 while PM10 is -0.33. Our study is not consistent with the conclusion in the previous study (10), which showed no significant relationship between PM10 and HFMD (10).…”
Section: Discussioncontrasting
confidence: 99%
“…Undoubtedly, it is a key factor in the development of disease. In the first stage, we pooled the overall cumulative effect of 21 cities which showed an approximately "M"-shape which was consistent with the results in other studies (Minhang Distric: a suburban district of Shanghai; Ningbo city) [5,40]. The effect showed that the cumulative risk decreased when temperature was lower than 40th.…”
Section: Discussionsupporting
confidence: 79%
“…The epidemiological triangle emphasizes that pathogens, hosts and the environment are the three elements of disease, and that human health can be maintained unless the balance is broke. Besides, temperature can affect the survival and transmission of pathogen as well as human activities and behaviors [40][41]. Undoubtedly, it is a key factor in the development of disease.…”
Section: Discussionmentioning
confidence: 99%